Student's Perspective On Learning English Phonemes - Dini Mutia Havid; Iren Adina Rahmadani Tarigan; Yani Lubis (Pusat riset dan Inovasi Nasional, 2023)
Studying phonemes is a part of phonology, so writing this article is about learning basic phonemes. Phonemes are the basic level of phonological learning because phonemes are the smallest basic units that form the elements that make up speech sounds. Therefore, in this article we will study the basic phoneme which is the smallest functional unit of language. a phoneme cannot stand alone because a phoneme has no meaning, but its role is very important because a phoneme can distinguish meaning. For example, the phonemes [l] and [r]. If we separate these two phonemes, we will definitely not understand their meaning. A phoneme has an identity basis which is called the meaning distinguishing function of the sound units of language. The method used in this article is a method that collects information through questionnaires to analyze students' understanding of phonemic learning and draw conclusions about basic phonemic learning, whether learning is important and easy to understand.